Does head CT scan pathology predict outcome after mild traumatic brain injury?. Issue 1 (20th July 2012) - Lannsjö, M.; Backheden, M.; Johansson, U.; af Geijerstam, J. L.; Borg, J.
<x xml:space="preserve">Abstract</x> Background and purpose More evidence is needed to forward our understanding of the key determinants of poor outcome after mild traumatic brain injury (MTBI). A large, prospective, national cohort of patients was studied to analyse the effect of head CT scan pathology on the outcome. Methods One‐thousand two‐hundred and sixty‐two patients with MTBI (Glasgow Coma Scale score 15) at 39 emergency departments completed a study protocol including acute head CT scan examination and follow‐up by the Rivermead Post Concussion Symptoms Questionnaire and the Glasgow Outcome Scale Extended (GOSE) at 3 months after MTBI. Binary logistic regression was used for the assessment of prediction ability. Results In 751 men (60%) and 511 women (40%), with a mean age of 30 years (median 21, range 6–94), we observed relevant or suspect relevant pathologic findings on acute CT scan in 52 patients (4%). Patients aged below 30 years reported better outcome both with respect to symptoms and GOSE as compared to patients in older age groups. Men reported better outcome than women as regards symptoms (OR 0.64, CI 0.49–0.85 for ≥3 symptoms) and global function (OR 0.60, CI 0.39–0.92 for GOSE 1–6). Conclusions Pathology on acute CT scan examination had no effect on self‐reported symptoms or global function at 3 months after MTBI. Female gender and older age predicted a less favourable outcome. The findings support the view that other factors than brain injury deserve attention to minimize long‐term complaints after MTBI.